Overseeding Florida Lawns for Winter Color - Laurie E. Trenholm; Joseph Bryan Unruh (EDIS)
Overseeding is the practice of using a temporary grass that is seeded into the permanent lawn to provide winter color. While this practice is common on golf courses, athletic fields, and high-profile landscape areas, the principles also apply to homeowners who wish to have a green lawn year-round. It is important to remember, however, that this also entails year-round lawn maintenance. This document is ENH14, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 22, 2001. Revised September 2001.